Influence Of Service Quality And Prices Towards Customer Loyalty Of Cahaya Garden Pharmacy In Batam - Septi Heksiana; Nur Elfi Husda (LPPM Universitas Respati Indonesia, 2024)
Customer loyalty is required in the business world, special in pharmaceutical companies such as pharmacies. The purpose of this study was to choose the impact of the quality and price of the service on patient loyalty at the park's lighting pharmacy. The analysis solution used in this study is a multiplex analysis method. This survey is a quantitative survey using survey methods. This survey is intended for customers who have visited several times. The sampling solution uses targeted sampling by a total of 162 respondents. The data investigation solution used to answer the hypotheses is the multiple regression analysis method. The results of the survey explained that the quality of service variables had a positive and significant impact on customer loyalty. This is clear from the important quality of service values, and the calculated t value is more important than the table value t. Price variables have a significant positive impact on customer loyalty. This is important and is evident from the value t being more important than the value of table t. Based on this study, the Cahaya Garden pharmacy can improve the quality of services and monitor prices, so it must maintain stability and competitiveness and retain its customers. Keywords: service quality, price, customer loyalty.